2022
DOI: 10.3892/mmr.2022.12589
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of DPP4 promotes the proliferation and the activation of the CREB/aromatase pathway in ovarian granulosa cells

Abstract: Dipeptidyl peptidase 4 (DPP4) has been revealed to be upregulated in women suffering from polycystic ovary syndrome (PCOS), which is a common reproductive disorder. The present study was designed to investigate the effects of inhibition of DPP4 expression on the proliferation of ovarian granulosa cells as well as on the activation of the cAMP response element-binding protein (CREB)/aromatase pathway. The expression levels of DPP4 in rat serum samples with or without PCOS and ovarian granulosa cells (KGN cells)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Follicular dysplasia and ovulation disorder are the main causes of infertility of PCOS, which are associated with abnormal proliferation of GCs, inhibition of GC proliferation leaded to nutrient and communication de ciencies in oocyte development [7,25]. Some scholars have reported that DPP4 knockout promotes proliferation and activation of CREB/ aromatase pathway in GCs, thereby alleviating PCOS [39]. Recent accumulated evidence revealed that FDPS has been found to be involved in various biological functions and disease processes, such as FDPS regulates endothelial cell proliferation and autophagy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Follicular dysplasia and ovulation disorder are the main causes of infertility of PCOS, which are associated with abnormal proliferation of GCs, inhibition of GC proliferation leaded to nutrient and communication de ciencies in oocyte development [7,25]. Some scholars have reported that DPP4 knockout promotes proliferation and activation of CREB/ aromatase pathway in GCs, thereby alleviating PCOS [39]. Recent accumulated evidence revealed that FDPS has been found to be involved in various biological functions and disease processes, such as FDPS regulates endothelial cell proliferation and autophagy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Following anaesthetization with intraperitoneal injection of 2% pentobarbital sodium (40 mg•kg −1 ), the rat abdomen was opened, and blood samples 2-3 mL were obtained from the abdominal aorta. 30) Then, the liver tissue was dissected out for biochemical analysis. Finally, the unconscious rats were immediately decapitated.…”
Section: Introductionmentioning
confidence: 99%